Polarization reconfigurable ultrawideband antenna for cognitive radio applications. Issue 3 (28th January 2013) - Aboufoul, Tamer; Alomainy, Akram; Parini, Clive
Abstract A novel compact ultrawideband microstrip monopole antenna with reconfigurable polarization capability is presented. The antenna can be switched from linear polarization to right‐hand circular polarization (RHCP) or left‐hand circular polarization (LHCP). The measured 3‐dB axial ratio fractional bandwidth for the RHCP or the LHCP after reconfiguration is 59.5% from 5.9 to 10.9 GHz. The interest of the proposed antenna in cognitive radio systems is twofold. First, it can be used to add polarization sensing to the conventional frequency sensing. Second, there are the gains of using it to add polarization diversity in communication between cognitive devices. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 54:501–506, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27353